AVAILABILITY OF PRE-SCHOOLING AS AN EDUCATIONAL AND SOCIAL INDICATOR - Merkys, Gediminas; Bubeliene, Daiva; Čiučiulkienė, Nijole (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The research paper presents the results of a large-scale longitudinal study which aims to highlight pre-schooling social problems with the help of social indicators. For over a decade, the authors of the research paper have been developing a survey inventory aiming to determine the population’s satisfaction with the public service index. The tool includes 190 original survey indicators that represent all public services. 20 indicators are devoted to education; two of them represent pre-school education. These are: 1) assessment of the quality of pre-school services; and 2) the availability of a child's place in a kindergarten in a residential area (availability). The existing statistical norming base (not older than 2 years) includes 12 municipalities in Lithuania and 88 subdistricts. The total number of respondents is 16202 (n=16202). It has been cleared out that the residents consider the quality of the service "high", but its "availability" is considered to be poor. The statistical regularity found is common to all surveyed municipalities. There is a significant dispersion of measured indicators in separate municipalities and in the subdistricts. Facing the negative evaluation tendency of the “availability“ service some municipalities are more able to handle the problem. For this reason their experience is worth to analyze and to disseminate in a broader way. It is also worth to mention that the results of this study have much in common with EUROSTAT data. In Lithuania, the inclusion of 2-3 years old children in the education system is extremely poor, whereas the inclusion of preschoolers is largely universal. It is possible to state that poor situation of 2-3 years old children inclusion in the Lithuanian education system is related to the problems of Lithuanian social policy. In Lithuania, mother (or father) receives financial benefits for two years after the birth of a child. It is also possible to save one‘s job without receiving a payment for one year more. From the point of view of women's employment and equal opportunities policies, our discovered regularity testifies social policy dysfunctions at the macro national level which, on their turn, indicate a deep-seated demographic crisis in an EU country.